Determination of surface dose in pencil beam scanning proton therapy. Issue 5 (13th March 2020) - Kern, A.; Bäumer, C.; Kröninger, K.; Mertens, L.; Timmermann, B.; Walbersloh, J.; Wulff, J.
Abstract : Purpose/objective: Quantification of surface dose within the first few hundred water equivalent µm is challenging. Nevertheless, it is of large interest for the proton therapy community to study dose effects in the skin. The experimental determination is affected by the detector properties, such as the detector volume and material. The International Commission on Radiation Units and Measurements in its report 39 recommends assessing the skin dose at a depth of 0.07 mm. The aim of this study is the estimation of the absorbed dose at and around a depth of 70 µm. We used various dosimetric approaches in conjunction with proton pencil beam scanning delivery to determine the skin dose in a clinical setting. Material/methods: Five different detectors were tested for determining the surface dose in water: EBT3 and HD‐V2 GAFCHROMIC™ radiochromic film, LiF:Mg, Ti thermoluminescent dosimeter, IBA PPC05 plane‐parallel ionization chamber, and PTW 23391 extrapolation chamber. The irradiation setup consisted of quasi‐monoenergetic scanned proton pencil beams with kinetic energies of 100, 150, and 226.7 MeV, respectively. Radiochromic films were placed within a vertical stack and in wedge geometry and were analyzed with FilmQA Pro™ adopting triple channel dosimetry. The extrapolation chamber PTW 23391, which served as a reference in the current work, was used in a conventional ionization chamber setup with a fixed electrode gap of 2 mm. Three Kapton® entrance windows with thicknesses of 25, 50, and 75 µm were employed. Thermoluminescent dosimeters were provided as powder and were pressed onto a sheet of aluminum. Furthermore, the Monte Carlo code TOol for PArticle Simulation (TOPAS) in version 3.1.p2 was used to model an IBA pencil beam scanning nozzle and score dose to water in a water phantom. Results: The resulting depth dose curves were normalized to their 100% dose at the reference depth of 3 cm. We obtained the skin doses with the extrapolation chamber and with TOPAS. For the experimental approach this resulted in 79.7 ± 0.3%, 86.0 ± 0.6%, and 87.1 ± 0.1% for the proton energies 100, 150, and 226.7 MeV, respectively. The results for TOPAS were 80.1 ± 0.2% (100 MeV), 87.1 ± 0.5% (150 MeV), and 86.9 ± 0.4% (226.7 MeV), respectively. Based on the experimental results of the skin dose, we provided a clinically relevant surface extrapolation factor for the common measurement methods. This allows the result of the first measurement depth of a detector to be scaled to the dose at the skin depth. Most practical would be the use of the surface extrapolation factor for the PPC05 chamber, due to its direct reading, the wide availability in clinics and the low uncertainties. The calculated factors were 0.986 ± 0.004 for 100 MeV, 0.961 ± 0.008 for 150 MeV, and 0.963 ± 0.003 for 226.7 MeV. Conclusions: In this study, dissimilar experimental approaches were evaluated with respect to measurements at depths close to the surface. The experimental depth dose curves are in good agreement with the simulation with TOPAS Monte Carlo. To the author's knowledge this was the first experimental determination of the skin dose according to the International Commission on Radiation Units and Measurements 39 definition in proton pencil beam scanning.